Medpropozicijskost z vidika družljivosti glagolov oz. povedkov ﻿ - Žele, Andreja (Slavia Centralis, 2020)
Inter-proposition from the point of view of verbal or predicative optionalityAs the co-reference of propositions within a complex sentence or text, interproposition enables the inter-dependent co-occurrence of predicates or, rather, predicative optionality, as well as relative meanings, which are marked by connectors. This article treats inter-proposition from the standpoint of possible predicative co-occurrences within a sentence.
Keywords: inter-proposition; predicative co-occurrence; verbal categories